Tinjauan Interpretatif Terhadap Aspek-Aspek Institusional dalam Implementasi Layanan Elektronik: Studi Kasus PT. XYZ - Agung Darono; Lukito Edi Nugroho; Warsun Najib (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
This research aims to determine what institutional aspects that can influence the organization to implement electronic services. This research used qualitative-interpretive research method with single case study research strategy. The findings of this research were: (1) the type of institutional pressures (normative / mimetic / coercive) that surround the organization and the business impact of these pressures determines the response / action of organization isomorphism; (2) the organization uses its institutional logic to perform isomorphism and the result was the decision to develop an electronic service as one of the steps to face existing institutional pressures. This research also proposed a framework which are expected to be used by an organization to identify the institutional aspects related to the implementation of electronic services as a mechanism to respond to these pressures by appropriate isomorphism action.